Horticultural activity predicts later localized limb status in a contemporary pre‐industrial population. Issue 3 (27th March 2017) - Stieglitz, Jonathan; Trumble, Benjamin C.; Kaplan, Hillard; Gurven, Michael
Abstract: Objectives: Modern humans may have gracile skeletons due to low physical activity levels and mechanical loading. Tests using pre‐historic skeletons are limited by the inability to assess behavior directly, while modern industrialized societies possess few socio‐ecological features typical of human evolutionary history. Among Tsimane forager‐horticulturalists, we test whether greater activity levels and, thus, increased loading earlier in life are associated with greater later‐life bone status and diminished age‐related bone loss. Materials and Methods: We used quantitative ultrasonography to assess radial and tibial status among adults aged 20+ years (mean ± SD age = 49 ± 15; 52% female). We conducted systematic behavioral observations to assess earlier‐life activity patterns (mean time lag between behavioural observation and ultrasound = 12 years). For a subset of participants, physical activity was again measured later in life, via accelerometry, to determine whether earlier‐life time use is associated with later‐life activity levels. Anthropometric and demographic data were collected during medical exams. Results: Structural decline with age is reduced for the tibia (female: −0.25 SDs/decade; male: 0.05 SDs/decade) versus radius (female: −0.56 SDs/decade; male: −0.20 SDs/decade), which is expected if greater loading mitigates bone loss. Time allocation to horticulture, but not hunting, positively predicts later‐life radial status ( β Horticulture  = 0.48, p  = 0.01), whereas tibial status is not significantly predicted by subsistence or sedentary leisure participation. Discussion: Patterns of activity‐ and age‐related change in bone status indicate localized osteogenic responses to loading, and are generally consistent with the logic of bone functional adaptation. Nonmechanical factors related to subsistence lifestyle moderate the association between activity patterns and bone structure.